Kiai Leadership in Implementing Religious Moderation in Islamic Boarding Schools - Parmoko, Parmoko; Muntholib, Muntholib; Badarussyamsi, Badarussyamsi (Center for Religious Studies and Social Empowerment Foundation, 2024)
This article reveals the implementation of religious moderation as a hidden curriculum at the Al-Ishlah Islamic Boarding School, Jambi Province. This article comes from ethnographic research with a qualitative qualitative approach. The results of this research show that the factors behind religious moderation in this Islamic boarding school include; haliyah, ibrah, amtsal, syawir, and culture. The implementation of attitudes and values that reflect religious moderation in this Islamic boarding school is reflected in the attitudes and behavior of national commitment, tolerant attitudes, non-violence attitudes, and accommodating attitudes towards local culture. Barriers to religious moderation revolve around the institutional environment, fanaticism, family, and information media. The results achieved in implementing religious moderation in the hidden curriculum are found in the curriculum, teachers' personalities and students. The implementation of religious moderation that has been implemented in the hidden curriculum is reflected in the Islamic education model which is holistic and inclusively integrative spiritually based. Artikel ini mengungkap implementasi moderasi beragama sebagai hidden kurikulum di Pondok Pesantren Al-Ishlah Propinsi Jambi. Artikel ini berasal dari penelitian etnografi dengan pendekatan kualitatif kualitatif. Hasil penelitian ini menunjukkan bahwa faktor yang melatarbelakangi moderasi beragama di pondok pesantren ini antara lain; haliyah, ibrah, amtsal, syawir, dan kultur. Implementasi sikap dan nilai yang mencerminkan moderasi beragama di Pesantren ini tergambar dalam sikap dan perilaku komitmen kebangsaan, sikap toleran, sikap anti kekerasan, sikap akomodatif terhadap budaya lokal. Hambatan moderasi beragama berkisar pada lingkungan lembaga, fanatisme, keluarga, dan media informasi. Hasil yang dicapai dalam penerapan moderasi beragama pada hidden kurikulum terdapat dalam kurikulum, pribadi guru, dan santri. Implementasi moderasi beragama yang telah diterapkan dalam hidden kurikulum tercermin dalam model pendidikan Islam yang berbasis spiritual holistik dan inklusif integratif.